A Two Switch Non-Isolated High Gain DC-DC Converter - Bussa V.K.; Singh R.K.; Mahanty R. (My University, 2025)
In this paper, a two switch non-isolated high gain DC-DC converter at low duty operating region with reduced number of elements is proposed. It is derived from a single-phase quasi Z-source inverter with necessary changes; two controlled switches of the inverter bridge are replaced by diodes, one of the capacitors of impedance network is replaced by a diode and AC filter inductor is eliminated for the DC operation. A comparative analysis among the proposed converter and some of the high gain DC-DC converters is given in terms of voltage gain and number of elements. Steady-state behavior of the proposed converter is verified through PSIM based simulation results along with the scaled down laboratory prototype experimental results. © 2018 IEEE.